Transporte aéreo doméstico: uma análise econômica para o período recente - Silva, Alexandre Manoel Angelo da (2001)
This dissertation aim to provide an economic analysis of the Domestic Airline Transportation (DAT) Industry's cost structure in Brazil. With this objective in mind this work proposes in chapters 1 and 2, respectively, a description of the institutional framework of the DAT Industry and an economic description of this Industry. This analysis provides, among other conclusions, an answer about the quantity of enterprisers that the Domestic Airline Transportation Industry must comprise. The estimation of the parameters of the proposed cost function is based on a panel data with months costs of the brazilian airline companies between august of 1998 and December of 1999.The estimation is based on Seemingly Unrelated Regressions (SUR), which adjusts for additive heterocedasticity, as proposed by Mandy & Martins-Filho (1993).